Recent Advances in Metabolomics - E. Smith, Robert; Tran, Kevin; M. Richards, Kristy (Current Metabolomics, 2015)
The field of metabolomics has continued to expand rapidly in the past two years. It has become an important part of personalized, predictive, preventive, and participatory (P4) medicine. In this article, recent advances in analytical methods (capillary electrophoresis, gas chromatography, liquid chromatography, mass spectrometry and MS imaging) are described. Advances in data analysis, quality control and receiver operator characteristic (ROC) curves are also described. The recent uses of metabolomics in disease diagnosis, epidemiology, epigenetics, hypertension, cancer, toxicology, drug discovery and the understanding of biological processes are also presented.
Keywords: capillary electrophoresis